The Urgence of Making a Shareholders List on Limited Company - Haryanti, Nurul Laksmita; Anggoro, Teddy (Budapest International Research and Critics University, 2021)
The purpose of this study is to find out the legal consequences if a company does not make a Shareholder Register, the second is to know the Notary's Responsibilities in making any Deed that does not have a Shareholder Register. This study uses a normative juridical writing type by using secondary data sources. The results of this study that the Board of Directors is obliged to make a Register of Shareholders, related to the legal consequences if this is not done, it is not regulated in the Company Law, then it is considered that there was negligence on the part of the Board of Directors because this is an obligation of the Board of Directors. Furthermore, the Notary's Responsibilities in the preparation of any Deed for which there is no Register of Shareholders that the responsibilities of the notary prior to the making of the deed relate to the notary's thoroughness and prudence in viewing and examining documents according to the facts.